Suplementasi Partikel Nano Ekstrak Black Garlic terhadap Tekanan Darah dan Kadar Glutathione (GSH) pada Ibu Hamil dengan Hipertensi Gestasional - Aldo, Mutia Perdana Hairun Nisa; Mardiyono, Mardiyono; Fatmasari, Diyah (Journal of Telenursing (JOTING), 2024)
The purpose of this study was to analyze the effectiveness of black garlic extract nano particle supplementation on blood pressure and glutathione (GSH) levels in pregnant women with gestational hypertension. This research method uses a True Experiment with Pretest-Posttest Control Group Design consisting of 2 groups, namely the intervention group consisting of 16 people. The results of the study showed a p-value = 0.000 (p <0.05) which means that black garlic extract supplementation is effective in reducing blood pressure and increasing glutathione (GSH) levels in pregnant women with gestational hypertension. In conclusion, black garlic extract nanoparticles are effective in lowering blood pressure and increasing glutathione (GSH) levels in pregnant women with gestational hypertension. Keywords: Gestational Hypertension, Pregnant Women with Hypertension, Black Garlic Nano Particles